STATUS AND SOCIAL ORGANIZATION OF HATINH LANGUR (Trachypithecus hatinhensis Dao, 1970) IN DONG HOA AND THACH HOA COMMUNES FOREST, QUANG BINH PROVINCE - Thanh Hai, Dong; A Tung, Thao (Journal of Forestry Science and Technology, 2018)
Hatinh Langur (Trachypithecus hatinhensis Dao, 1970) is endemic to Central Vietnam and Laos. In Vietnam, this species is restricted to two provinces of Quang Binh and Quang Tri. The species is nationally and globally threatened. Previous studies have shown that the social structure of leaf-eating monkeys is one-male or multimales and multifemales units. Group size ranges from 7 to 20 individuals. Studies on the social structure of T. hatinhensis are mostly carried out in Phong Nha - Ke Bang National Park, while other sites only investigate the status and distribution of species. The objective of this study was to determine the population status and social organization of the Hatinh langur in Dong Hoa and Thach Hoa Forest as a basis for proposing conservation measures. Linetransects and direct count methods was used to collect data. The results showed that there were 9 groups with the total number of 81 individuals. Social organization of groups of T. hatinhensis is similar to those patterns of species in subfamily colobinae that comprise of one-male and multimales and mutifemale units. Average group size is 9 ± 3 individuals. The ratio of adult males to females (AM/AF) is 1:2.5; infants to females (IF/AF) is 1:3; adults to immature individuals is 1:0.84.